The Effect Of Push Up And Fins Training On 50 Meter Freestyle Swimming Speed At The Dholpin Swimming Club - Oscar Diosi Sisata Putra (Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of push-up and fins training on the speed of 50 meters freestyle swimming at the Dolphin Swimming Club. This type of research is experimental research with a sample of 10 athletes. The results of the study showed that push-up training significantly influenced the increase in the speed of 50 meters freestyle swimming of Dolphin Swimming Club athletes, showing that the t-count (1.40) > t-table (1.042). Fins training significantly influenced the increase in the speed of 50 meters freestyle swimming of Dolphin Swimming Club athletes, showing that the t-count (1.14) > t-table (1.042). There was a significant difference in the effect between push-up training and fins training on increasing the speed of 50 meters freestyle swimming of Dolphin Swimming Club students with the results showing that t-count (1.49) > t-table (1.042), and fins training was better/more effective in the speed of 50 meters freestyle swimming of Dolphin Swimming Club athletes.